2001
DOI: 10.1021/la0015415
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation from Mixed Films of Rhodamine Dye and Arachidic Acid at the Air−Water Interface:  Correlation with Spectroscopic Properties

Abstract: Mixed insoluble monolayers of bis(N-ethyl,N-octadecyl)rhodamine perchlorate (RhC18) and arachidic acid (ArAc) at the air−water interface were characterized by surface pressure−area isotherm, second harmonic generation (SHG), and reflection spectroscopy studies. The analysis of surface pressure−area isotherms of mixed RhC18/ArAc layers provided evidence that there was a high degree of miscibility of film components and a strong interaction among them. A new band was found to appear on the blue side of the refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…These fluctuations are attributed to the nonhomogeneity of the molecular monolayer. The formation of molecular aggregates during monolayer compression is common and has been reported previously ,, for various types of molecules. In the case of the PL monolayer, BAM measurements, see Figure , were performed to illustrate this point.…”
Section: Resultssupporting
confidence: 53%
“…These fluctuations are attributed to the nonhomogeneity of the molecular monolayer. The formation of molecular aggregates during monolayer compression is common and has been reported previously ,, for various types of molecules. In the case of the PL monolayer, BAM measurements, see Figure , were performed to illustrate this point.…”
Section: Resultssupporting
confidence: 53%
“…2,[5][6][7][8][9][10][11]13 In particular, it was found that the RhC 18 chromophore adopted a tilted orientation at the air/water interface. 11 It was also reported that a variety of aggregated species, whether fluorescent or nonfluorescent dimers and aggregates, were formed in RhC 18 monolayers during compression and in RhC 18 -lipid LB films.…”
Section: Introductionmentioning
confidence: 99%
“…Monolayers of amphiphilic molecules bearing a chromophoric moiety, in particular, those belonging to the xanthene dye family, have attracted considerable attention for many years for both scientific and practical reasons. As their photophysical properties are sensitive to the organization of chromophores at the interface, dye monolayers provide ideal model systems to study orientational arrangement, molecular aggregation, and energy transfer processes between molecules residing in restricted geometry. Besides, dye monolayers are used as precursors of multilayered films built up with the Langmuir−Blodgett (LB) deposition technique . Therefore, the study of the chromophore arrangement at the air/water interface, which provides the ability to elucidate, predict, and control 2D molecular organization, is crucial in the intelligent design of well-ordered and defect-free films for various applications in such areas as molecular electronics, optical devices, and sensors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations